2008
DOI: 10.1097/md.0b013e318173aa56
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Manifestations in Patients With Limited Systemic Sclerosis and Centromere Protein-B (CENP-B) Antibodies

Abstract: Audiovestibular dysfunction has been reported in patients with connective tissue disease. Systemic sclerosis (SSc; scleroderma) is a rare connective tissue disease of unknown etiology. In the current study we assess whether audiovestibular involvement is present in patients with limited scleroderma (lSSc). To answer this question we studied a series of 35 consecutive patients who fulfilled well-established classification criteria for lSSc and had antibodies against the major centromere protein-B (CENP-B), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 45 publications
5
46
0
10
Order By: Relevance
“…Of the eight studies that investigated changes, all identified hearing loss in most individuals with SS, and the prevalence in this finding ranged from 20 to 77%. The type of hearing loss was bilateral sensorineural (6,(9)(10)(11)13,16,17) in most cases, corroborating the physiopathology of the systemic disease. However, mixed (11,15,17) and unilateral (13,17) hearing loss were also described in few cases.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Of the eight studies that investigated changes, all identified hearing loss in most individuals with SS, and the prevalence in this finding ranged from 20 to 77%. The type of hearing loss was bilateral sensorineural (6,(9)(10)(11)13,16,17) in most cases, corroborating the physiopathology of the systemic disease. However, mixed (11,15,17) and unilateral (13,17) hearing loss were also described in few cases.…”
Section: Resultsmentioning
confidence: 60%
“…Amor-Dorado et al (12,17) and Maciaszczyk et al (13) had differences in the study population with regard to the form of disease (limited or diffuse); however, only in the analysis by Amor-Dorado et al (12) results were presented by considering the type of disease. Prevalence of changes in the vestibular system was higher for patients with diffuse SS (Charts 1 and 2).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations